PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN TERHADAP PEMAHAMAN SISWA PADA MATERI MENGATASI BERBAGAI MACAM UJIAN DAN COBAAN DI MAN KOTA PALANGKA RAYA - Abdul Aziz; Siti Badriah; Aulia Pratama Putra; Salsabila Ananda; Norhalijah Lira Fitria (ADIBA : JOURNAL OF EDUCATION, 2024)
This research aims to develop learning video media to improve MAN Palangka Raya City students' understanding of the material for dealing with various kinds of tests and trials. The research method used is research and development (R&D) with a 4D model (Analysis, Design, Develop, Disseminate). The research subjects involved MAN Palangka Raya City students. The definition stage includes needs analysis, student characteristics, curriculum and materials. The design stage includes creating storyboards, scripts and visual video designs. The development stage consists of video production, material and media expert validation, and limited testing. The dissemination stage is carried out through the introduction of video media in classroom learning. Validation results from material experts show a percentage of 83.3%, which is categorized as very feasible. Meanwhile, validation from media experts received a score of 84%, also included in the very worthy category. The questionnaire given to teachers received a score of 85.5%, and the questionnaire given to students received a score of 76.5% which was categorized as adequate. The use of learning video media has been proven to increase students' understanding significantly, as shown by increased results before and after the test. This research concludes that the development of educational video media will help increase students' understanding at MAN Palangka Raya City about how to approach various kinds of tests and trials from an Islamic perspective.